A CONTRIBUTION TO THE STUDY OF MILAN ZLOKOVIĆ’S ARCHITECTURE IN BELGRADE FROM THE INTERWAR PERIOD - Bankovic, Angelina (Arhitektura i urbanizam, 2021)
Architect Milan Zloković, his life and work, were often subjects of research in numerous published papers. He was presented as a pioneer of modern movement in Serbian architecture and one of its most prominent representatives, as well as one of the most eminent Serbian architects in the first half of the 20th century. His extensive opus, which is stated to contain just over 170 designs, was analyzed in detail. However, during the musealization process of his legacy, as a part of formation of Bequest of Milan Zloković, in cooperation of Belgrade City Museum and Milan Zloković Foundation, over 50 previously unknown designs were identified. That is a result of extensive research of vast project documentation, preserved in his family house, which was unavailable for previous researchers. This paper presents one part of that research, specifically designs for several objects in Belgrade, originating from the interwar period. In its first part, short presentation of Zloković’s biography is given, especially facts concerning period treated here, from 1925 to 1937. The second part is dedicated to the designs, every of which is presented separately. They are divided into two segments, first concerning built objects, and second unrealized projects. Among built objects, few of alteration and extensions are presented, too. The paper is mostly based on study of primary sources, designs from the Milan Zloković’s legacy and documentation from the Historical Archive of Belgrade, as well as previously published researchs.